A new foreign direct investment accounting methodology for economic development organizations - Henry Loewendahl (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
Official FDI statistics are based on balance of payments data and the equity share of the foreign entity. This Perspective argues that the official method of measuring FDI is not suitable for economic development organizations, and outlines eight key components of a new methodology to measure FDI for economic development.
Keywords: 330